Kajian Indeks Bahaya Seismik Regional Menggunakan Data Seismik Pulau Jawa Tahun 1900-2006 - Sulistiyani S; Sorja Koesuma; Nugroho Budi W (Department of Physics, Sebelas Maret University, 2016)
It has been conducted a research about Regional Seismic Disaster Index (RSDI) in Java Island by using seismic data from 1900 – 2006. RSDI is a index showing vulnerability seismic disaster in an area. The hight risk area is the highest risk, the low area is the lowest risk. The highest RSDI areas were Banten, Jawa Barat, and D.I Yogyakarta Provinces. While the lowest RSDI areas were DKI Jakarta and Jawa Tengah Province. Deviations standard value showed the moving RSDI value each region. Region with big RSDI value had high Seismic level were Banten , Jawa Barat, and D.I. Yogyakarta Province.